Contamination Profile of DDTs in the Shark Somniosus microcephalus from Greenland Seawaters - Cotronei, Salvatore; Pozo, Karla; Audy, Ondřej; Přibylová, Petra; Corsolini, Simonetta (Bulletin of Environmental Contamination and Toxicology, 2018)
DDT isomers were detected in all the liver and muscle samples of Greenland sharks Somniosus microcephalus (n = 15) caught in Greenland seawaters. The mean concentrations of ΣDDTs (sum of o,p’ and p,p’ DDT, DDD, and DDE isomers) were 1094 ± 818 ng/g lipid weight (lw) in the muscle and 761 ± 416 ng/g lw in the liver. The p,p’-DDE accounted for 48% ± 41% and 53% ± 54% of the total DDT residue in the white muscle and liver, respectively. The lipid content was 48% ± 10% in the muscle and 43% ± 17% in the liver. Female sharks showed the highest concentrations of ΣDDTs. The youngest shark showed higher concentrations of ΣDDTs in the liver than the older sharks. To our knowledge, this is one of the few investigations on DDT levels in S. microcephalus where concentrations were correlated to lipid content and sex/size.